Answer:
(14, -9)
Explanation:
So you can solve this using substitution. When you're solving a systems of equations, you're looking for when (x, y) is the same for both equations, or in other words where the two linear equations intersect. Because of this we can solve for x or y in one equation and substitute it into the other equation, since the x and y in one equation should equal the x and y in the other equation.
Original equation:
x + 2y = -4
Subtract 2y from both sides
x = -2y - 4
Original equation:
2x + 3y = 1
Substitute -2y -4 as x
2(-2y - 4) + 3y = 1
Distribute the 2
-4y - 8 + 3y = 1
Combine like terms
-y - 8 = 1
Add 8 to both sides
-y = 9
Multiply both sides by -1
y = -9
So now that you know what y is, you can plug it into either equation to solve for x:
x + 2y = -4
Plug in -9 as y
x + 2(-9) = -4
Multiply
x - 18 = -4
Add 18 to both sides
x = 14
So this gives you the solution (14, -9)